Samoocena zdrowia, jakości życia i zaradności życiowej osób starszych = Self-evaluation of health, quality of life and resourcefulness of life in elderly people - Jopkiewicz, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is the subjective evaluation of health, quality of life and resourcefulness of life by elderly people in respect to age, gender, and education, place of living and material situation. The study was conducted in 2010 on the areas of small and large districts in Świętokrzyskie and Mazowieckie Provinces. It comprised 186 people over the age of 60, including 106 women and 80 men who were divided into three age groups: 60-69 years of age, 70-79 years of age and 80+.
Keywords: self-assessment of health; quality of life; resourcefulness of life; elderly people; samoocena stanu zdrowia; jakość życia; zaradność życiowa; osoby starsze